0048 Evening Blue-depleted Hospital Environment: The Effects On Melatonin. (27th April 2018) - Vethe, D; Langsrud, K; Scott, J; Engstøm, M; Olsen, A; Salvesen, Ø; Mathusiak, B; Sand, T; Morken, G; Kallestad, H
Abstract: Introduction: We have built a new psychiatric intensive care unit to optimize patients circadian rhythms using a tunable light system. All light sources in half the unit (patient rooms, bathrooms, corridors, and common areas) are depleted of blue light between 1830h to 0700h, at other times the light is normal. The other half has normal light at all times. We aimed to test the effect of living in the evening blue-depleted hospital environment on melatonin suppression and melatonin onset phase shift. Methods: In a randomized crossover trial, 12 healthy participants were admitted for 10 days, 5 days in each light environment. Hourly saliva samples were collected from 19:00h to 23:00h on five evenings. The evening before admission (baseline), and the evening after each condition, melatonin was assessed in dim light (<3 lux). The final evening in each condition, melatonin was assessed in the blue-depleted and the normal environment. Melatonin suppression was calculated using the AUC during the final evening in each environment divided by the AUC during the following night in dim light. Phase shift was the difference in timing of dim light melatonin onset (>4pg/ml) between the last assessment and the baseline assessment. The effect of 'condition' on suppression and time for melatonin onset was estimated using a linear mixed model. The combination of assessment, condition and time was taken as the fixed effect and participant as the random effect. Results: Melatonin levels were less suppressed in the blue-depleted environment, by 15% (95% CI -2% - 34%) compared to 45% (95% CI 33% - 59%) in the normal environment (p = 0.007). Melatonin onset was phase advanced by 1:45h (95% CI 1:25 - 2:04) after living in the blue-depleted environment compared to 0:35h (95% CI 0:11 - 1:04) after the normal environment (p < 0.001). Conclusion: It is possible to create a hospital environment that has an impact on melatonin secretion and the circadian clock. This may improve treatment outcomes in patient groups with disrupted circadian rhythms, and may be important for how inpatient units are designed. Support (If Any): N/A.